Carotenoids in dehydrated persimmon: Antioxidant activity, structure, and photoluminescence - González, Cristina M.; López-García, Adrián; Llorca, Empar; Hernando, Isabel; Atienzar, Pedro; Bermejo, Almudena; Moraga, Gemma; Quiles, Amparo (Elsevier, 2021)
In this study, the effect of two hot air drying conditions (40 °C for 23 h and 60 °C for 9 h) on the content, antioxidant activity, microstructure, and luminescence properties of persimmon carotenoids in three ripening stages was studied. Based on the results from total carotenoids content and HPLC analysis, the carotenoid's content increased with the advance of ripening, highlighting the β-cryptoxanthin fraction. In addition, drying treatments did not affect the carotenoid content and profile but decreased the antioxidant activity. Microstructural studies showed that the ripening progress and/or drying treatments, led persimmon tissues to lose integrity, allowing the diffusion of carotenoids and their degradation. Photoluminescence measurements evidenced the synthesis of β-cryptoxanthin during the fruit ripening. After drying, a new emitting specie at 340 nm was attributed to the carotenoid's isomerisation while the emission at 500 nm experienced a shift that was related to the formation of thermal degradation products. Both facts could explain the loss of antioxidant activity in persimmon submitted to drying treatments. In this sense, photoluminescence, in combination with spectrophotometric, chromatographic and structural techniques, helps to understand the phenomena caused by both, ripening and drying treatments, in the persimmon's carotenoids fraction.